Penerapan Asuhan Berpusat Pada Perempuan Dalam Asuhan Kebidanan Berkelanjutan Nyonya S Di Puskesmas Sewon 1 Bantul - Rana Dhiya Fadhilah; Eka Nur Rahayu; Riadini Wahyu Utami (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Maternal and child health is a problem in Indonesia and even the world. It isproven in the Sustainable Development Goals (SDG's), one of the goals in the healthsector is to improve the welfare of mothers and children. In addition, according to theIndonesian Ministry of Health in 2015, the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) each year reached 450 per hundred thousand live births.However, this can still be prevented by providing appropriate and intensive care to theclient. One of the intensive care is comprehensive care. Comprehensive midwiferycare if done properly can prevent or detect early complications that will occur in themother. The client is Mrs. S, she has one risk, which is over 35 years old, so it is arisky pregnancy. Midwives in the case of midwifery students provide comprehensivemidwifery care. Students are able to apply continuous midwifery care from pregnancyto the puerperium to Ny. S at Sewon 1 Health Center Bantul. The care provided duringpregnancy is pregnancy massage because Mrs. S several times complained offatigue. During childbirth the author provides care by teaching the mother breathingrelaxation techniques and motivating the mother. During the postpartum period, themother was worried because her breast milk had not yet come out, so she was givenoxytocin massage and motivation for the mother. During the neonatal period, Mrs. Shad experienced jaundice, the care provided was to breastfeed the baby to the motherand recommended breastfeeding at least every 2 hours even though the milk had notcome out. Continuing midwifery care has been provided to Mrs. S by taking intoaccount the various risk factors that Mrs. S and the baby.Keywords: Continuity of Care, Pregnancy Massage, Oxytocin Massage